Religious Verse in Leningrad Samizdat: Origins and Confluences (ENTHYMEMA International journal of literary criticism, literary theory, and philosophy of literature, 2015)
Religious, in particularly Christian imagery, was ubiquitous in Leningrad samizdat poetry of the 1970s. This essay addresses two main questions that are closely related: is the term «religious verse» appropriate for this kind of poetry; how are we to define «religious» in this case? Secondly, what were the common denominators of religious verse in 1970s Leningrad.